1994
DOI: 10.1111/j.1469-8137.1994.tb04016.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different nutrient regimes on the regulation of carbon metabolism in Norway spruce [Picea abies (L.) Karst.] seedlings

Abstract: SUMMARYPhosphoenolpyruvate carboxylase (PEPC) activity, fructose 2,6-bisphosphate (F26BP), starch and soluble sugar contents were determined in needles and roots of Norway spruce seedlings grown in a semi-hydroponic cultivation system under difFerent nutrient regimes. In needles, a surplus of nitrogen caused an increase in specific PEPC activity {up to six times control activity) and F26BP content (up to tbree times control level) while starch content was reduced. Sucrose contents were not affected. Basically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…It is commonly accepted that conifers assimilate nitrogen in their roots [41] and that PEPC is the enzyme of carbon metabolism primarily regulated by nitrogen availability [55]. In addition, Wingler and coworkers [61] have demonstrated that PEPC activity in roots of spruce seedlings is higher than in the corresponding cotyledons under most of the nitrogen conditions they used in their experiments. Based on these data it can be suggested that PEPC is a basic component of the N-fixation cascade in the roots of spruce and that the high PEPC activity is attended by an enhanced expression of the ppc gene corresponding to the PAPPC 14/2 cDNA and/or a higher ppc mRNA stability in this tissue.…”
Section: Discussionmentioning
confidence: 96%
“…It is commonly accepted that conifers assimilate nitrogen in their roots [41] and that PEPC is the enzyme of carbon metabolism primarily regulated by nitrogen availability [55]. In addition, Wingler and coworkers [61] have demonstrated that PEPC activity in roots of spruce seedlings is higher than in the corresponding cotyledons under most of the nitrogen conditions they used in their experiments. Based on these data it can be suggested that PEPC is a basic component of the N-fixation cascade in the roots of spruce and that the high PEPC activity is attended by an enhanced expression of the ppc gene corresponding to the PAPPC 14/2 cDNA and/or a higher ppc mRNA stability in this tissue.…”
Section: Discussionmentioning
confidence: 96%
“…There is ample evidence that nitrogen supply is a potent activator of PEPC (Wingler et al, 1994), simultaneously causing a decrease in the sucrose phosphate synthase (SPS). Thus the C flow might be directed away from the synthesis of sucrose towards that of amino acid (Champigny & Foyer, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Fructose 2,6-bisphosphate was extracted in a buffer containing 100 mM y^-mercaptoethanol at pH 10 and 5% polyvinylpolypyrrohdone (PVPP), and assayed through the activation of pyrophosphate fructose 6-phosphate kinase according to Wingler et al (1994). Extraction and determination of ATP and ADP were based on the method described by Hampp (1985).…”
Section: Methodsmentioning
confidence: 99%